Enhancing the quality of Final Year Projects in Computing through weekly written tasks - Marion Bowman (Association for Learning Development in Higher Education (ALDinHE), 2012)
Writing can be used as a means of engaging students in their studies, leading to greater time spent on the subject, greater interest in the subject and ultimately better grades. The intervention discussed in this paper involved the setting of weekly written tasks embedded within the lecture strand of a Computing Final Year Project (FYP) module. The aims behind this Ã¢â¬Ëthinking through writingÃ¢â¬â¢ intervention were to enhance studentsÃ¢â¬â¢ ability to produce high quality projects and written project reports, as well as to improve studentsÃ¢â¬â¢ ability to manage their time while completing their projects. Results from this study showed that there was a significant positive relationship between weekly task marks and project marks, however, only 57% of the cohort were classed as being Ã¢â¬ËengagedÃ¢â¬â¢ in doing the written tasks (as they had completed seven or more of the ten tasks). In addition, tentative results showed that the weekly task intervention seemed to be associated with better quality written project reports. Also, students generally seemed to regard the weekly written tasks as useful for time management, in terms of completing their written project reports. However, this collaborative intervention did raise questions about the link between learning and writing in this context. Finally, a number of recommendations are made for Ã¢â¬Ëlearning through writingÃ¢â¬â¢ interventions in FYP modules.